Impact of etiology on disease course in chronic pancreatitis - Murillo, Katharina; Simsek, Onur; Göltl, Philipp; Wekerle, Maximilian; Hardt, Philip; Gubergrits, Natalia; Hetjens, Svetlana; Ebert, Matthias; Schneider, Alexander; Hirth, Michael (Pancreatology, 2023)
Background: Complications in chronic pancreatitis (CP) can be grouped in inﬂammatory (ICC) and ﬁbrotic (FCC) clusters and pancreatic insufﬁciency cluster (PIC). However, the association between etiological risk factors and the development of complication clusters remains obscure. In this study, the impact of the etiology and disease duration on disease onset and development of complications was investigated. - Methods: This cross-sectional study recruited patients with CP from Mannheim/Germany (n ¼ 870), Gieben/Germany (n ¼ 100) und Donetsk/Ukraine (n ¼ 104). Etiological risk factors, disease stage, age at disease onset, complications, need for hospitalization and surgery were noted. - Results: In 1074 patients diagnosed with CP, main risk factors were alcohol and nicotine abuse. An earlier onset of the disease was observed upon nicotine abuse (À4.0 years). Alcohol abuse was only associated with an earlier onset of the deﬁnite stage of CP. Alcohol abuse was the major risk factor for the development of ICC (p < 0.0001, multiple regression modeling). Abstinence of alcohol reduced ICC, whereas abstinence of nicotine showed no association. PIC correlated with efferent duct abnormalities and the disease duration. In contrast, FCC was mainly dependent on the disease duration (p < 0.0001; t-test). The presence of any complication cluster correlated with the need for surgery (p < 0.01; X2-test). However, only ICC correlated with a prolonged hospital stay (p < 0.05; t-test). - Conclusions: ICC is mainly dependent on alcohol abuse. In contrast, FCC and PIC are mainly dependent on the disease duration. The etiology and disease duration can be used as predictors of the course of disease to provide individual treatment and surveillance strategies.